Self‐directed reflective assessment for collective empowerment among pre‐service teachers. (11th October 2020) - Yang, Yuqin; Du, Yang; van Aalst, Jan; Sun, Daner; Ouyang, Fan
Abstract : Abstract: This study investigated the role and process of self‐directed reflective assessment (SDRA) enhanced by learning analytics to support pre‐service teachers' (PTs') collective empowerment in a knowledge‐building (KB) classroom. The participants were 43 second‐year PTs from a compulsory course taught by a teacher who had 2 years' teaching experience. A comparison class of 47 PTs, taught by the same teacher and studying the same topics in a regular KB environment, also participated. Statistical analysis revealed significant differences in participation and domain understanding between the experimental class and the comparison class. Qualitative tracing of the SDRA group's online discourse indicated that the PTs were empowered and that their collective empowerment increased gradually over time. Analysis of the PTs' prompt sheets revealed that analytic‐supported SDRA helped the PTs engage in collective decision making to choose and judge promising ideas, and in collective synthesis and "rise‐above" of ideas, thus helping them engage in high‐level collective empowerment. The findings have important implications for the design of technology‐rich environments as metacognitive tools to support learners' empowerment, and they shed light on how teachers can use such tools to engage learners in metacognitive practices to increase their empowerment. Practitioner Notes What is already known about this topic? Empowering pre‐service teachers' (PTs') to master higher order competencies is particularly important; PTs' empowerment primarily consisted of these high‐level competencies. Collaborative inquiry that can help learners to develop higher order competencies and further empowerment primarily depends on learners' metacognition. SDRA has great potential in empowering PTs, however, little research has been conducted to investigate the role and process of SDRA for supporting PTs. What this paper adds SDRA can empower PTs and help them increase their empowerment over time. SDRA effectively drives PTs to actualize and develop their metacognition, which in turn fosters PTs to engage in collective decision making, idea negotiation, and idea synthesis and "rise‐above" thinking, and thereby gradually helps the PTs increase their empowerment. The design of learning environments, which capitalizes on KB pedagogy and SDRA, is accessible to the PTs and fosters their collective empowerment. Implications for practice and/or policy Establishing a democratic and collaborative learning environment, fostering a sense of community and confidence among learners, and helping learners to gradually develop necessary skills are important for supporting their empowerment. The learning design for empowering learners should support learners' agency, collective decision making, reflection and regulation, and collective KB. It is important to organize collective reflection opportunities to help students engaged in data‐supported SDRA.